IMPROVING STUDENTS’ CRITICAL THINKING SKILLS ON HYDROCARBON MATERIAL THROUGH ASSESSMENT FOR LEARNING - Al Halwi, Adam; Muchlis, Muchlis (Universitas Labuhanbatu, 2025)
Purpose–This study describes the effectiveness of implementing the Assessment for Learning (AfL) approach to improve students' critical thinking skills on hydrocarbon materials.Methodology–This study is a pre-experimental research with a one-group pre-test-post-test design. The effectiveness of implementing AfL was analyzed based on the pre-test and post-test results of students' critical thinking skills on hydrocarbon materials. Data were analyzed using the completeness criteria of learning objectives, N-gain scores, and mean difference tests.Findings–The Paired t-test results resulted in a p-value of 0.000 (< 0.05), indicating a significant difference between the pre-test and post-test scores. As many as 100% of students got an N-gain score in the high category. The study results showed that ≥ 85% of students were in the complete category. Thus, implementing AfL has proven effective in improving students' critical thinking skills on hydrocarbon materials.Significance–This study contributes to the development of chemistry education by demonstrating the effectiveness of implementing AfL in enhancing students' critical thinking skills, particularly in learning about hydrocarbon material.